Estimation of project completion time using wiener random process and Bayesian structure based on expert's point of view - Hajialinajar, M. T.; Rahimi, H.; Mosavi, M. R.; Afandak, B. (The Journal of the Operational Research Society, 2019)
One of the important issues in project control is the estimation of project completion time. High accuracy in estimation can have a significant effect on project evaluation cost. Therefore, presenting a suitable method for estimation is essential. By definition, a project is a temporary work that is done just once in order to create a specific product or service. Therefore, the structure of a project (especially long term projects) has many uncertainties. Using the Wiener random process, with regard to the updating structure of its distribution based on expert's point of view and new observation data, is a studied subject in this paper. Finally, by applying the data of a real case study, the benefits of estimation method has been shown and its results have been studied.